THE IMPACT OF WORK LOAD AND WORK STRESS ON EMPLOYEE ORGANIZATIONAL COMMITMENTS MOBILE SAKTI COMPANY - Eric Hermawan, Madha Komala, Corry Yohana (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research aims to improve employee organizational commitment at Sakti Mobile Company, by analyzing the effect of workload on work stress, analyzing the effect of workload on organizational commitment, analyzing the effect of work stress on organizational commitment and the effect of workload through work stress on organizational commitment. Collecting data using a questionnaire and a sample of 113 people with SEMPLS analysis. The results showed that: (1) workload has a direct and positive effect on work stress, (2) workload has a direct and positive effect on organizational commitment, (3) work stress has a direct and positive effect on organizational commitment, and (4) workload direct and positive effect through work stress on organizational commitment. In addition, the emphasis in this research is that to increase organizational commitment is to pay attention to workload, either directly or indirectly through work stress.